Use of Artificial Intelligence in Teaching and Learning Environment: A case of using Chat GPT - Dhakal, Aishwarya Prashad; Devkota, Bipana (NPRC Journal of Multidisciplinary Research, 2024)
This paper review and analyzed research paper to examine how artificial intelligence (AI) is incorporated into teaching and learning environment. The integration of Artificial Intelligence in teaching and learning environments offers significant opportunities to enhance educational experiences for both students and educators. AI technologies, such as adaptive learning systems, intelligent tutoring, and automated administrative tools, are transforming traditional teaching methods by providing personalized, data-driven learning experiences. The results demonstrate AI's innovatory impending to improve teaching strategies, elevate student interest, and make difficult subject matter easier to understand and perform their duty and response. Intellectual tutoring systems, robotics, and generative AI models like Chat GPT are some of the solution; AI technologies that have been investigated. These solutions address long-standing issues in teaching and learning by enabling interactive problem-solving settings, real-time feedback, and individualized learning experiences. It has also point out certain drawbacks, such as moral dilemmas, difficulties in putting the plan into practice, and contextual restrictions in various learning environments. The purpose of this paper is to identify the use of artificial intelligence in academia especially in teaching and learning environment. In order to gain optimize the advantages of artificial intelligence in educational field while minimizing its drawbacks, the study emphasizes the significance of a well-rounded strategy that blends technological innovation with flourishing pedagogical approaches. This thorough analysis lays the groundwork for further study and real world implementations, especially in underserved areas, to promote the widespread use of AI in educational learning and teaching.